2010
DOI: 10.1016/j.bandc.2010.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Biases of spatial attention in vision and audition

Abstract: Neurologically normal observers misperceive the midpoint of horizontal lines as systematically leftward of veridical center, a phenomenon known as pseudoneglect. Pseudoneglect is attributed to a tonic asymmetry of visuospatial attention favoring left hemispace. Whereas visuospatial attention is biased toward left hemispace, some evidence suggests that audiospatial attention may possess a right hemispatial bias. If spatial attention is supramodal, then the leftward bias observed in visual line bisection should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 70 publications
(93 reference statements)
4
30
0
Order By: Relevance
“…Some potential bias may also be introduced by the reported human tendency to misperceive the midpoint of the angular distance between two horizontally distinct sound sources. Several authors have reported the midpoint to be located 1° to 2° rightward (Cusak et al, 2001;Dufour et al, 2007;Sosa et al, 2010), although this shift may be modulated by listener handedness. For example, Ocklenburg et al (2010) observed a rightward shift for left-handed listeners and a leftward shift for right-handed listeners.…”
Section: Accuracy and Precision Of Auditory Localizationmentioning
confidence: 97%
“…Some potential bias may also be introduced by the reported human tendency to misperceive the midpoint of the angular distance between two horizontally distinct sound sources. Several authors have reported the midpoint to be located 1° to 2° rightward (Cusak et al, 2001;Dufour et al, 2007;Sosa et al, 2010), although this shift may be modulated by listener handedness. For example, Ocklenburg et al (2010) observed a rightward shift for left-handed listeners and a leftward shift for right-handed listeners.…”
Section: Accuracy and Precision Of Auditory Localizationmentioning
confidence: 97%
“…It is well established that visuospatial attention in neurologically normal subjects is also distributed asymmetrically, resulting in a modest but systematic and significant leftward deviation of perceived line midpoint (PSE) in line bisection tasks (Bradshaw & Nettleton, 1983; Bradshaw, Nettleton, Nathan & Wilson, 1985; Bradshaw, Nathan, Nettleton, Wilson & Pierson, 1987; McCourt & Olafson, 1997; McCourt & Jewell, 1999; Jewell & McCourt, 2000; McCourt, Garlinghouse & Slater, 2000; McCourt & Garlinghouse, 2000a;b; McCourt, 2001; McCourt, Freeman, Tahmahkera-Stevens & Chaussee, 2001; McCourt, Garlinghouse & Butler, 2001; Foxe, McCourt & Javitt, 2003; McCourt, Garlinghouse & Reuter-Lorenz, 2005; McCourt, Shpaner, Javitt & Foxe, 2008; Leone & McCourt, 2010; Sosa, Teder-Sälejärvi & McCourt, 2010). It leads also to a systematic overestimation of stimulus saliency (e.g., size, brightness, and numerosity) in the left versus right visual hemifield (Luh, Rueckert & Levy, 1991; Nicholls, Bradshaw & Mattingley, 1999; Charles, Sahraie & McGeorge, 2007), to a differential ability to detect changes within the left visual half of complex visual stimulus arrays (Iyilikci, Becker, Gunturkun & Amado, 2010; Du & Abrams, 2010), and to a selective enhancement of memory for objects located within the left half of scenes (Dickson & Intraub, 2009; Della Sala, Darling & Logie, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, 4 of the 9 participants used by Gori et al, (2014) had lost sight due to retinopathy of prematurity, which has been associated with poorer spatial performance as compared to other early and congenitally blind individuals (Eardley, Edwards, Maloin & Kennedy, 20152016). Of the other research described above, Ocklenburg et al (2010), Sosa et al, (2010), Dufour et al, (2007) and Gori et al, (2014) showing that the leftward bisection bias is reduced or reversed in far space (McCourt & Garlinghouse, 2000;Bjoertomt et al, 2002;Longo & Lourenco, 2010;Gamberini et al, 2008;Longo & Lourenco, 2006Lourenco & Longo, 2009;Varnava et al, 2002) draws into question the comparability of auditory results using extrapersonal stimuli with standard peripersonal tactile and visual line bisection tasks. As a consequenceConsequently, there remains considerable debate about whether leftward auditory pseudoneglect is underpinned by a supramodal system (e.g.…”
Section: Introductionmentioning
confidence: 88%
“…dextrals pointed to the left of the sound source and sinistrals to the right (see also Corral & Escera, 2008). Sosa, Teder-Sälejärvi and McCourt (2010) created a forced-choice line bisection task. Sosa et al (2010) found, like Dufour, Touzalin and Candas (2007), that the bias in judgement of auditory space was significantly rightward of the midpoint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation